Air Connectivity and Airport Infrastructure in Northern Canada - Alexandre G. de Barros; Marcela Coelho Lopes; Iyad Sahnoon (The School of Public Policy Publications)
To analyze the existing air transportation infrastructure that could potentially benefit from the Canadian Northern Corridor, a list of remote communities was obtained and investigated. A total of 182 communities have been assessed by Transport Canada or the provinces and territories, of which 146 are located inside the proposed Canadian Northern Corridor area. These communities are the focus of our study to answer the following questions: